Find the least value assumed by z if z = x 2 + 2 x y + 3 y 2 + 2 x + 6 y + 4
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nice approach!
z = ( x + y + 1 ) 2 + 2 ( y + 1 ) 2 + 1
Clearly at x = 0 and y = − 1 , both square expression becomes zero , hence : z m i n = 1
Problem Loading...
Note Loading...
Set Loading...
One more method of doing it except completing the square.
First differentiate w.r.t to x and set it equal to 0 .Repeat the same w.r.t y .
d / d x ( x 2 + 2 x y + 3 y 2 + 2 x + 6 y + 4 ) = 2 x + 2 y + 2 = 0 . . . ( 1 )
d / d y ( x 2 + 2 x y + 3 y 2 + 2 x + 6 y + 4 ) = 2 x + 6 y + 6 = 0 . . . ( 2 )
Solving 1 and 2,
x m i n = 0
y m i n = − 1
z m i n = 1